The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.4314/bajopas.v4i2.34
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Germination and Growth Behavior of Some Cowpea Varieties Using Neem (Azadiracta Indica) Leaf Water Extracts

Abstract: The experiment was conducted to observe the inhibitory effects of the leaf extract derived from neem (Azadiracta indica) on germination and growth behavior of some cowpea varieties (receptor). Experiments were set on sterilized petridishes with a photoperiod of 24 hours at room temperature of 27-30 o C. The effects of the different concentrations of aqueous extracts were compared with distilled water (control). The aqueous extracts of leaf caused significant inhibitory effects on germination, root and shoot el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 11 publications
(4 reference statements)
0
8
0
Order By: Relevance
“…The filtrate was centrifuged and supernatant was decanted (Prasad et al, 2011). The filtrate was defined as 100 per cent extract and was further diluted with distilled water at 25 , 50, 75, 100 per cent concentrations (Nikneshan et al, 2011) while distilled water was used as control T1 (0 %) (Lawan et al, 2011).…”
Section: Plant Materials and Preparation Of Aqueous Extractsmentioning
confidence: 99%
“…The filtrate was centrifuged and supernatant was decanted (Prasad et al, 2011). The filtrate was defined as 100 per cent extract and was further diluted with distilled water at 25 , 50, 75, 100 per cent concentrations (Nikneshan et al, 2011) while distilled water was used as control T1 (0 %) (Lawan et al, 2011).…”
Section: Plant Materials and Preparation Of Aqueous Extractsmentioning
confidence: 99%
“…A) General view of normal maize germination (B) Abnormal germination: note the maize kernel emerging above soil level Elsewhere, [9,10] working on Arapu leaf powder (Albizia amara) and Moringa oleifera found that Arapu leaf powder maintained good seed viability and seedling vigour for scented rice stored for up to 20 months however, Moringa oleifera had serious allelopathic effects on the viability and germination of Vigna radiata where germination decreased with increasing concentrations of Moringa leaf extracts. [11] Also, working on cowpea found that Neem leaf water extracts inhibited germination as well as suppressed the growth and development of some cowpea varieties with increasing concentrations of neem leaf extracts. These findings agree with the work of [12,[16][17].…”
Section: (B)mentioning
confidence: 99%
“…Furthermore, these plant materials offer an ecologically safer means of controlling insect pest infestations in stored cereals and grains in the tropics where the resource poor farmers are generally found [8]. Such materials include powders and extracts from several plant species namely, drumstick tree Moringa oleifera [9][10][11][12][13]. These materials have been established to be environmentally friendly bio-pesticides and possess many desirable properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The filtrate was defined as 100 per cent extract (Nikneshan et al, 2011). From this 25, 50, 75, 100 per cent concentrations were prepared and distilled water was used as control (Lawan et al, 2011). The treatments were replicated five times in completely randomized design (CRD).…”
Section: Plant Materials and Preparation Of Aqueous Extractsmentioning
confidence: 99%